Memanfaatkan Teknologi Web untuk Efisiensi Stok Pupuk dalam Pertanian Berkelanjutan - Gunawan Prayitno; Ratna Sari (Jurnal Teknologi dan Informatika, 2024)
Sustainable agriculture faces a major challenge in maintaining the availability and efficient use of fertilizers. Information technology, particularly web applications, has the potential to optimize fertilizer stock management, improve productivity, and enhance household food security for farmers. This study aims to analyze how web technology can improve the efficiency of fertilizer stock management in sustainable agricultural practices. Through literature review and interviews with stakeholders, this research identifies the benefits of web technology in fertilizer stock management, such as improved accuracy in demand forecasting, minimized stock losses, and increased timeliness in fertilizer distribution. The results show that web-based information systems can integrate production data, stock, and fertilizer needs, facilitating decision-making and supporting real-time fertilizer distribution. The implementation of this technology provides significant benefits for farmers, web technology developers, and policymakers, and contributes to efficient and environmentally friendly sustainable agricultural practices.